Disciplining religion: the role of the state and its consequences on democracy - Cesari, Jocelyne (Journal of religious and political practice, 2016)
This article presents the concept of hegemonic religion and its relationship with democracy. This concept entails not only a certain type of institutional relation between state and religion but, more importantly, a kind of national culture with religion at its core. Utilizing Norbert Elias's figurational sociology, this article analyses how postcolonial states have built a national habitus that plays a decisive role in the politicization of religion. It focuses on examples from Islam and Buddhism and discusses how hegemonic types of politicised religions have negative impacts on democracy.